Energy citizenship through crises: Analysis of citizens’ letters - Havukainen, Minna (European Journal of Sustainable Development, 2025)
The EU believes citizens should have a central role in the globally significant energy transition. The concept of energy citizenship recognizes citizens as active participants in the energy system instead of passive consumers. In principle, energy citizenship refers to perceived empowerment to decide energy use. The concept is expected to have a role in tackling climate change. Traditionally energy transition has been mainly seen as technological progress supported by financial and regulatory instruments. These instruments have been efficient, especially in increasing renewable energy production. While energy consumption habits have been studied extensively, the perceived empowerment to make decisions about energy use has not been adequately addressed in studies. This study extends and categorizes the concept of energy citizenship by shedding light on citizens' personal experiences during the energy crisis and its connection to being active citizens. The data consists of qualitative data from citizens' letters written after the Russian invasion in Ukraine. The study found four different types of energy citizenship: authoritarian, follower, sobriety, and technocratic enlightening the acceptance of energy policy. Keywords: Energy transition, energy citizenship, energy crisis